Concomitant crown dilaceration and concrescence in maxillary incisors following trauma to their primary predecessors: A case report - Madiraju G Shekhar; Yousef M Almugla; Rohini Mohan; Basil M AlNasser (Journal of Pharmacy and Bioallied Sciences, 2023)
Developmental disturbances in the permanent dentition are commonly seen due to traumatic injuries to the primary teeth, especially intrusive and avulsion injuries of the overlaying primary incisors. These disturbances may range from enamel discoloration or hypoplasia, crown/root dilaceration, odontoma-like malformation and eruption disturbances. Concrescence is extremely rare in anterior teeth. This case report describes a rare case that showed a concrescence of the unerupted maxillary right lateral incisor and maxillary central incisor with crown dilaceration. Awareness regarding early diagnosis and the consequences of untreated trauma to primary teeth should be emphasized.